Destination selection for education tourism service quality, destination image and perceived spirituality embedded model - Rahman, Muhammad Sabbir; Osman-Gani, AAhad M.; Raman, Murali (Emerald Publishing Limited, 2017)
Purpose – The purpose of this research is to empirically examine the critical factors that are influencing international students’ perception in the selection of a destination for education tourism. Design/methodology/approach – This research seeks to develop a comprehensive framework embedded with service quality, destination image and spirituality behavior. The data were collected by administering a self-administered questionnaire to a sample of 220 respondents who were studying at the universities in Peninsular Malaysia. The constructs and items used in the questionnaire were adapted from the literature review. This research applied confirmatory factor analysis and structural equation modeling to test the proposed hypotheses. Findings – The outcome of this research indicated that there is a substantial relationship between service quality and the choice of a destination for education tourism. This research also explored that destination brand image significantly relates to the selection of a destination for education, tourism when the destination loyalty variable plays a strong mediation role. Interestingly, the direct relationship between spirituality behavior and selection of destination was not significant. On the other hand, a significant relationship was discovered between spirituality behavior and choice of destination when the tourists’ intention plays as a mediating function. Research limitations/implications – First, the limitation is in the scope of this study, as only five constructs were examined. Future research may include other types of variables in exploring the antecedents of destination selection for education tourism. Second, the sample size was only 220 and respondents were restricted to only a few universities. Future research should be done on a bigger sample size and on more diverse sample. Practical implications – Managers of the respective higher learning institutions need to focus on tourists’ satisfaction by providing a memorable experience. International students who have satisfactory experience with the respective higher learning institutions will spread a positive word of mouth about the destinations to other prospective foreign students. Today, tourists have a strong urge to see the spiritual side of their liveliness. Policymakers need to offer services with the comportment of the spiritual settings in their respective educational environment to extend the spiritual experience toward international students. Social implications – There is a need for more research on how to build a comprehensive model for selection of a destination in educational tourism. The results of this empirical research are of particular significance to policymakers, as it better informs them as to how best to use the antecedents in designing the destination choice for education tourism to establish it as more practical regardless of the diverse spiritual beliefs. Originality/value – This research is one of the initial attempts on part of the researchers in Malaysian education tourism context where spirituality has been taken into consideration.